2011
DOI: 10.3109/14764172.2011.564625
|View full text |Cite
|
Sign up to set email alerts
|

Laser scar revision: A review

Abstract: Surgery, burns, wounds, and inflammatory processes can lead to the development of a variety of different scars. Scars are categorized as hypertrophic, keloid, atrophic and acne scars. Different treatments are utilized for each scar type. The evolution of scar treatment has led to the advancement of lasers for the improvement of all scar types. Non-ablative lasers such as the pulsed dye laser have been shown to be effective in the treatment of hypertrophic and erythematous scars. Ablative lasers, the carbon dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Several different nonablative laser options such as 1,320-nm Nd:YAG or 1,450-nm diode lasers have demonstrated the efficacy in the treatment of atrophic scars, but the degree of clinical improvement is far less than that of the ablative systems. 10 For a treatment of surgical scars, PDL, ablative, and nonablative fractional lasers (NAFLs) have been reported to be effective. One article mentioned the superiority of 1,550-nm NAFL compared with PDL on postoperative scars, and others reported the clinical effect of the PDL followed by AFL on surgical scars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different nonablative laser options such as 1,320-nm Nd:YAG or 1,450-nm diode lasers have demonstrated the efficacy in the treatment of atrophic scars, but the degree of clinical improvement is far less than that of the ablative systems. 10 For a treatment of surgical scars, PDL, ablative, and nonablative fractional lasers (NAFLs) have been reported to be effective. One article mentioned the superiority of 1,550-nm NAFL compared with PDL on postoperative scars, and others reported the clinical effect of the PDL followed by AFL on surgical scars.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the 585-nm PDL showed a low improvement and 595-nm PDL showed a moderate improvement on hypertrophic scars. 10,11 Recontouring of atrophic scars with the use of CO 2 and Er:YAG lasers has become very popular in recent years. Their goal is to smooth the texture and stimulate collagen production by selective ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Ablative laser therapy can serve as adjuvant procedure [21,22]. Atrophic scars improve after several sessions with the erbium-YAG laser.…”
Section: Discussionmentioning
confidence: 99%
“…Erbium-YAG lasers have been among the first effective lasers in the treatment of atrophic acne scars [22]. In a study from Turkey on 128 patients with acne scars the investigators observed improvement of skin texture, scars and pigmentation [24].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because the healing process of acne-associated lesions following inflammation involves a change in the dermis specifically associated with the characteristics of this particular dermal lesion. Lasers, fractional and unfractionated, ablative (CO 2 ) and a variety of nonablative systems, have been reported for the treatment of acne scars [2][3][4][5]. However, the ablative laser approach is associated with the problem of a high incidence of hyperpigmentation, especially in Japanese skin types III and IV, and the nonablative approach suffers in terms of the efficacy in reaching the deeper layers of the dermis, absolutely required in the treatment of acne scars.…”
Section: Introductionmentioning
confidence: 99%